O037 Future informed consent research – a step in the wrong direction!. (22nd July 2022) - Clements, JM; Convie, LJ; Kirk, SJ; Clarke, M
Abstract: Introduction: Over 300 million invasive procedures occur globally every year, each requiring patient informed consent. No single outcome measure exists for measurement of the informed consent process. A core outcome set (COS) for informed consent for therapy consisting of 9 outcomes has been developed to define what outcomes matter to key stakeholders in the informed consent process. We aimed to identify the frequency of uptake of the COS consent outcomes in future randomised control trials. Methods: A systematic review of prospectively registered randomised control trial protocols was performed. The online trial registries World Health Organisation (WHO) International Clinical Trials Registry Platform (ICTRP) and the US National Library of Medicine ClinicalTrials.gov were searched. All studies assessing interventions designed to improve the informed consent process were considered. Results: 627 registered protocols were identified of which 22 met the inclusion criteria. Only two core outcomes were reported in any prospective interventional consent trial protocols. Patient satisfaction with the consent process and patient satisfaction with the amount of information were observed which employed unvalidated tools. Patient knowledge was the predominant primary outcome measure (n=20). Unvalidated measurement tools were used in all cases. Patient anxiety, decisional regret and decisional conflict were the only outcomes consistently measured using validated measurement tools. Conclusion: The use of unvalidated outcome measurement tools in future consent trials are widespread. This review has highlighted the clear disconnect between chosen outcomes in future consent trial protocols and an established informed consent COS, limiting the potential value of outputs in future consent trials. Take-home message: A clear disconnect exists between the outcome measures used in prospective consent randomised trials and an established core outcome set for informed consent for therapy.